Hydrochemistry and Contamination in Sedimentary and Fractured-Rock Aquifers of The Upper Rio Negro Basin – Amazonas/Brazil - Fernandes Neto, Lucindo Antunes; Wahnfried, Ingo (Anuário do Instituto de Geociências, 2024)
The Amazon region has the largest hydrographic network on the planet. However, cities and communities along rivers obtain water from tube wells without studying the chemical quality and, consequently, the potability of their water. In specific geological contexts, there is a significant probability of natural contamination by arsenic in groundwater in the region, already attested in previous works in the Solimões, Madeira and Amazonas rivers basins, but not yet found in the Negro river basin. As the Negro is the second largest river in the Amazon Basin, it has become necessary to study the chemical quality of its groundwater, relating it to the geology of the region. In this work, water samples were collected from 21 wells and 4 water springs used for human consumption, following the protocols proposed by the US – EPA. In the field, the physicochemical parameters of the in-situ water were measured, and alkalinity tests were carried out on the samples. The cations were analyzed at INPA and the anions at the Geological Survey of Brazil (SGB). From the 25 samples, 16 had analises results within acceptable ionic balance values, and 12 of the 16 had at least one of the following elements in concentration above World Health Organization and Brazilian Guideline Values: Al, As, Fe, Mn and Pb. The presence of values below the GV, but above what is considered natural, of NO3- in 66% of the contaminated points, associated with the shallow depth of most of the wells, installed in areas of recent sedimentary deposits and that do not show any or few signs of care demonstrate that the contamination in these localities is of anthropic origin. Two samples (16% of the contaminated samples) are from deep wells installed in fractured aquifers, which in this case indicate contamination of geogenic origin. Arsenic was found in association with iron and aluminum in a well installed in alluvial sediments, which indicates that more studies are needed for this specific geologic formation to know the quality of this water. For other locations and cities, short, medium and long-term measures are needed to prevent anthropogenic contamination of aquifers.